Formação de professores em uma escola da zona rural do município de Uberlândia: das necessidades formativas à formação contínua - Santos, Ivana Ferreira dos (2019)
This master's degree research is included in the research line of Educational Knowledge and Practices of the Post-Graduation Program in Education of the Federal University of Uberlândia and deals with the training needs of primary education teachers who work in a rural school in the municipality of Uberlândia, in the state of Minas Gerais. The ongoing training process analyzed in this study refers to 2015 and 2016, a period in which public policy in the municipality was being implemented with the legal apparatus of Law No. 11.444/2013, which established the Municipal Public Network for the Right to Teach and Learn. The general objective of this study was to identify and analyze the training needs of teachers who work from the 1st to the 9th year responsible for the various curricular contents, with the purpose of offering subsidies for the development of in-service training programs. In order to identify other researches developed in the educational field on the training needs of teachers, we did a bibliographical survey to know terms and concepts inherent to the teaching profession, the training of teachers and the relationship with the training needs that are directly involved in the teaching and learning process. Important theoretical contributions, such as Borges (2013), Campos (2017), Freire (1979, 1996, 2001, 2015), Gatti and Barreto (2009), Gatti, Barreto and André (2011), Imbernón (2000, 2009,2011), Nóvoa (1991, 1992, 1995, 2009), Pimenta and Almeida (2011), Rodrigues and Esteves (1993) and Tardif (2002, 2013), provided an opportunity to broaden the analysis and reflection on the subject of research. The theoreticalmethodological route was based on exploratory research with a qualitative approach, from the documentary and empirical analysis. The instrument for the construction of the data was chosen with the intention of giving voice to the teachers, so that they could reflect on the relevance of (re) definition of more significant formative actions to the pedagogical work performed by them. Therefore, we opted for the questionnaire with open and closed questions. Participating subjects are effective teachers of the professorship who have been working for more than five years in the school researched. The results of the research revealed that teachers have an interest in participating in continuing education courses but want to contribute to the construction of these processes, acting as subjects that move and manifest themselves according to their training needs, which go through the theory-practice unit and for a differentiated look at educational field. We consider that the participation of teachers in the planning of training actions was an essential contribution to broaden the research conditions, discussions to highlight new forms of work and educational practice of education professionals. We conclude that research is relevant because it contributes to studies about the political and social role of teachers, since their knowledge, mobilized in pedagogical practices, in general, becomes a reference in the learning process in basic education.